Pengaruh Investment Opportunity Set (IOS) Dan Good Corporate Governance (GCG) Terhadap Kinerja Keuangan - Susanti, Susi (Universitas Muhammadiyah Tangerang, 2021)
Abstarct. This study aims to obtain findings about the Effect of Investment Opportunity Set and Good Corporate Governance simultaneously on Financial Performance, Effect of Investment Opportunity Set and Good Corporate Governance partially on Financial Performance. The research design used in this research is quantitative. The subjects of this research are cement manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the objects in this study are the Investment Opportunity Set, Good Corporate Governance and Financial Performance in cement manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The results of this study indicate that in the simultaneous and significant test of the Investment Opportunity Set and Good Corporate Governance on Financial Performance, the significance value of the F test is less than 0.05 or 0.004 <0.05 and the F count is greater than F table 2, 53 or 14,182 > 2.53. While in the partial test the Investment Opportunity Set has a significant and significant effect on Financial Performance, with a significance value of t test less than 0.05 or 0.000 <0.05 and t count greater than t table 2.004 or -7.488 < 2.004.